2002
DOI: 10.1097/01.mp.0000030451.28828.00
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Cushing’s Disease Caused by Pituitary Adenoma Producing Adrenocorticotropic Hormone and Growth Hormone Concomitantly: Aberrant Expression of Transcription Factors NeuroD1 and Pit-1 as a Proposed Mechanism

Abstract: A 53-year-old Japanese woman was diagnosed with Cushing's disease caused by a adrenocorticotropic hormone (ACTH)-secreting pituitary adenoma on the basis of clinical an imaging data. The surgically resected tumor tissue was investigated histopathologically using immunohistochemical analysis of pituitary hormones. Our study revealed that the adenoma expressed not only ACTH but growth hormone (GH) in the tumor cells. Furthermore, immunohistochemical double staining showed that some adenoma cells were positive fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…A conjunction of two pituitary tumors may imply common genetic and molecular mechanisms of tumorigenesis. Tahara et al reported that pituitary transcription factors such as NeuroD1 and Pit-1 were aberrantly expressed in pituitary adenomas secreting ACTH and GH concomitantly [9]. The expression patterns of pituitary transcriptional factors may reveal the origin and development of tumor cells, and future studies should examine this possibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A conjunction of two pituitary tumors may imply common genetic and molecular mechanisms of tumorigenesis. Tahara et al reported that pituitary transcription factors such as NeuroD1 and Pit-1 were aberrantly expressed in pituitary adenomas secreting ACTH and GH concomitantly [9]. The expression patterns of pituitary transcriptional factors may reveal the origin and development of tumor cells, and future studies should examine this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Although several combinations of hormonally-functioning double pituitary adenomas have been reported [4][5][6][7][15][16][17][18][19][20][21][22][23][24][25][26][27][28], the coexistence of acromegaly and pituitary Cushing's disease is rare [3,[8][9][10][11] (Table 4). Although our case resembles previous cases in terms of the immunohistochemical staining pattern, ours differs in the lack of Cushingoid features (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Since either immunohistochemical study using double staining, electron microscopic study, or clonal analysis was not performed in this case, it remains unknown whether GH, PRL, and ACTH are synthesized in the same or different cells, and whether the tumor cells are monoclonal or polyclonal. It has been reported that two transcription factors, NeuroD1 and Pit-1, are aberrantly co-expressed in the same pituitary tumor cells with ACTH and GH production, respectively [9], suggesting their potential roles in the differentiation into ACTH-and GH-producing cells. Thus, such translineage co-expression of transcription factors (NeuroD1, Pit-1) may be responsible for the multihormone synthesis as in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it might be considered that GH and CRF family neuropeptides were produced concomitantly from the same cells although the double stains for GH and CRF family peptides were not examined. Tahara et al reported a case in which ACTH and GH were concomitantly produced from the pituitary adenoma [24]. They showed the aberrant expression of transcription factors NeuroD1 and Pit-1 by in situ hybridization, and proposed it for the concomitant production of ACTH and GH.…”
Section: Immunohistochemistrymentioning
confidence: 99%